Ontologi Tutupan Lahan Sebagai Dasar Pemahaman Ekosistem Das yang Berkelanjutan - Dicky Artha; Mahludin S. Baruwadi; Hasim Hasim (Fakultas Teknik Universitas Cenderawasih, 2025)
Land cover change is one of the most critical environmental issues affecting the stability of watershed (DAS) ecosystems. This study aims to explore the existential nature of land cover through an ontological approach as a conceptual foundation for sustainable environmental management. A descriptive qualitative method was applied using literature analysis, conceptual mapping, and environmental philosophy interpretation. The results reveal that land cover change not only reflects ecological dynamics but also represents a transformation in the ontological relationship between humans and nature. Within the framework of ecological ontology, land is understood as a living entity possessing intrinsic value and existential function within the web of life. This interpretation is supported by recent studies (2015–2025) demonstrating significant links between land cover change, hydrological responses, and the decline of ecosystem service quality across Indonesia and Southeast Asia (Basuki et al., 2022; Supangat et al., 2023; Locke, 2024). Ontological awareness thus serves as a philosophical foundation for watershed management policies that are ecologically ethical, holistic, and sustainable.